Rantai Nilai Pariwisata Sumba Timur dan Sumba Barat Daya - Hary Jocom; Daniel Daud Kameo; Intiyas Utami; Viktor Bungtilu Laiskodat (LEMBAGA PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT AKADEMI PARIWISATA DENPASAR, 2021)
Currently the tourism sector is one of the development priorities in East Nusa Tenggara. In this regard, this article aims to discuss the dynamics of the tourism value chain in East Sumba and Southwest Sumba. This study used a descriptive qualitative method to describe the dynamics of the tourism value chain in the two districts on the island of Sumba. Data collection techniques through observation, transets, and in-depth interviews. The results of this study indicate that East Sumba and Southwest Sumba have diverse tourism potentials and unexplored natural resources. This potential and wealth has high selling value if it is managed professionally and sustainably by involving local communities. The problems of amenities, accommodation and tourism awareness of the local community are still the main obstacles. However, the value chain that supports the tourism industry has been built even though it is not yet fully functional. Thus, it is necessary to have a strategy and planning for future tourism development involving all stakeholders.